TYPICAL MITRAL VALVE CHORDAE TENDINEAE AND ABNORMALLY LOCATED CHORDAE TENDINEAE OF THE HUMAN HEART LEFT VENTRICLE - Fedonyuk, L.Ya.; Malyk, Yu.Yu. (World of Medicine and Biology, 2014)
Background. Modern morphological studies require high quality illustrative results that can be obtained by the methods of three-dimensional reconstruction and modeling.The modern method of investigation of the structure of biological tissues is laser polarimetry which uses different methods of analysis of the data, which are based on such fundamental concepts as the polarization properties of light that describes the coherence matrix. Material and methods. We have investigated the chordae tendineae of the left ventricles of the 45 human hearts of adults of mature age. For the study we used the histological methods, the method of three-dimensional modeling and method of laser polarimetry. Discussion of the results. This article describes the three-dimensional model of the structural organization of the typical mitral valve chordae tendineae and abnormally located chordae of the left ventricle of the human heart. And also describes the results of research by the method of laser polarimetry optical anisotropic properties of collagen fibers, elastic fibers and cardiomyocytes in the composition of typical and abnormally located chordae tendineae of the left ventricle of the human heart. The results show that the three-dimensional models of typical chordae tendineae of mitral valve and abnormally located chordae tendineae of the human left ventricular have differences in the structural organization. Typical mitral valve chordae tendineae formed by centrally located core that is surrounded by the peripherally located collagen-elastic layer which contains 3-5 magistral blood vessels that cross from the papillary muscles to the valve cusps. Abnormally located chordae tendineae are formed by 2-4 dense collagen cores, separated each other by the layer of loose connective tissue in which are located blood vessels of the microcirculation. Conducted researches anisotropic properties of collagen and elastic fibers in the composition of chordae tendineae of the human left ventricular found that elastic fibers characterized by different quantitative indicators the magnitude of anisotropy, which is diagnosed in the third-order statistical moments (asymmetry) Stokes vector parameter S4. For collagen fibers are typical manifestations ordered of hierarchical anisotropic architectonics with expressive statistical difference of the fourth order moment (excess). Conclusions. The investigations allowed receiving of new objective data concerning peculiarities of the chordae tendineae of the human left ventricle, through the creation of three-dimensional models of chordae tendineae, which provides possibility of the visualization of their internal content and interaction of structural components in the space. Research of chordae tendineae of the human left ventricle by laser polarimetry method allowed to conduct a systematic analysis of the topography of the anisotropic properties of collagen fibers, elastic fibers and cardiomyocytes obtained through the intensity distribution at different polarization orientations of images of parameter vector Stokes, polarization maps and Mueller matrix elements and their corresponding statistical moments of the 1-st – 4-th order.